2018
DOI: 10.1186/s12890-018-0700-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Shp2 ameliorates monocrotaline-induced pulmonary arterial hypertension in rats

Abstract: BackgroundSrc homology 2 containing protein tyrosine phosphatase (PTP) 2 (Shp2) is a typical tyrosine phosphatase interacting with receptor tyrosine kinase to regulate multiple signaling pathways in diverse pathological processes. Here, we will investigate the effect of Shp2 inhibition on pulmonary arterial hypertension (PAH) in a rat model and its potential cellular and molecular mechanisms underlying.MethodsMonocrotaline (MCT)-induced PAH rat model was used in this study. Phps-1, a highly selective inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We previously reported rare inherited LGD or D-Mis variants in CHD risk genes NOTCH1 ( n = 5), PTPN11 ( n = 1), and RAF1 ( n = 2) carried by APAH-CHD cases [ 18 ]. Specific inhibition of the protein encoded by PTPN11 (SHP2) [ 97 ], and induction of mir-204 which negatively targets SHP2 [ 98 ], improved right ventricular function in the monocrotaline rat model of PAH, suggesting a more general role of PTPN11 in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported rare inherited LGD or D-Mis variants in CHD risk genes NOTCH1 ( n = 5), PTPN11 ( n = 1), and RAF1 ( n = 2) carried by APAH-CHD cases [ 18 ]. Specific inhibition of the protein encoded by PTPN11 (SHP2) [ 97 ], and induction of mir-204 which negatively targets SHP2 [ 98 ], improved right ventricular function in the monocrotaline rat model of PAH, suggesting a more general role of PTPN11 in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pulmonary artery remodeling, including wall thickening, muscularization, and fibrosis of the outer membrane in pulmonary artery, eventually leading to right heart failure, was also an important pathological feature of PAH (Cajigas & Awdish, 2016; Hoette, Jardim, & Souza, 2010; Stenmark, Fagan, & Frid, 2006). In previous researches, the indexes of WT%, WA%, and infiltration of inflammatory were used to assess pulmonary artery remodeling (Cheng et al, 2018; Davies et al, 2012; Pickworth et al, 2017; Wu, Hao, et al, 2017; Zhang, Chang, Zhao, et al, 2019), and CSA of cardiomyocyte was used to assess right ventricular hypertrophy (Chen, Shen, et al, 2019; Chen, Wang, et al, 2019). In the current study, H&E staining results revealed that isorhamnetin not only reduced the abnormal increase of MCT‐induced WT% and WA% and CSA but also improved MCT‐induced pulmonary arterial wall thickness, increased luminal stenosis wall, and infiltration of inflammatory cells in rats.…”
Section: Discussionmentioning
confidence: 99%
“…We previously-reported rare inherited LGD or D-Mis variants in CHD risk genes NOTCH1 (n=5), PTPN11 (n=1) and RAF1 (n=2) carried by APAH-CHD cases (17). Specific inhibition of the protein encoded by PTPN11 (SHP2) (74), and induction of mir-204 which negatively targets SHP2 (75. ), improved right ventricular function in the monocrotaline rat model of PAH, suggesting a more general role of PTPN11 in PAH.…”
Section: While Effects Ofmentioning
confidence: 99%